A girl with doubts and a kind of daisies - Villamuza Manso, Noemí (Ondina - Ondine, 2020)
Before being who I am right now I have been a child, and it is there, in childhood, where monsters live. “Girls don’t protest, they don’t bother, they don’t have ambitions, they don’t contradict, girls respect, they help”. And they settle for it. I’m talking about me and what was feeding me subconsciously. I am the oldest of four sisters so set an example and condescend. I took it very seriously. As a consequence, playing was pushed right into the background because we had to be responsible instead...Illustrating is the way I have chosen to communicate, because now I play while I working, everything I hadn’t played as a child. Eighty percent of my work is aimed at girls and boys, but I also draw to rescue my own childhood, that time between clouds and suns, in which I grew up. Nowadays, a large part of the girls (most of the lucky ones from the West) grow up sharing soccer at school, openly protesting in the classroom in front of their male classmates, and I think they look ahead to the future more ambitiously than girls thirty or forty years ago. Although there is still a lot to do and even though we drag such a long patriarchal tradition, there are many awaked consciousness among students, educators and authors. I try to get boys approached to inspiring female figures, to make it easier for them to express their emotions and to value their female classmates since they start their school life. In order to reach this goal, my proposal is offering girls and young women literary and artistic tools that make them feel able to manage what they want to become. Key words: childhood, insecurity, sensitivity, value, creativity, force, example, mother